2021
DOI: 10.1108/ijoa-07-2020-2305
|View full text |Cite
|
Sign up to set email alerts
|

Homesickness: a comparative study of defense and civilian employees and individual differences

Abstract: Purpose Most of the studies in the field of homesickness are confined to students; this study aims to explore the feeling of homesickness among working professionals. Also, it tends to examine individual differences in the experience of homesickness across employees of different gender, ages, experience, family type, etc. The study also aspires to compare homesickness among military and civil employees. Design/methodology/approach The study explores five dimensions of homesickness, namely, missing family, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Consistent with prior studies, homesickness is higher among the elderly with lower education, lower monthly income, and manual labor occupations. 56,57 Higher educational attainment, income and job complexity are associated with better mental health. 58,59 In the spatiotemporal dimension, homesickness is higher among the elderly who migrated across provinces and with shorter periods of residence, which is consistent with the prior findings.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with prior studies, homesickness is higher among the elderly with lower education, lower monthly income, and manual labor occupations. 56,57 Higher educational attainment, income and job complexity are associated with better mental health. 58,59 In the spatiotemporal dimension, homesickness is higher among the elderly who migrated across provinces and with shorter periods of residence, which is consistent with the prior findings.…”
Section: Discussionmentioning
confidence: 99%
“…The review is based on “Homesickness: a comparative study of defense and civilian employees and individual differences,” by Garg et al (2022), published in International Journal of Organizational Analysis .…”
Section: Commentmentioning
confidence: 99%
“…A research paper by Garg et al (2022) investigates the feeling of homesickness among working professionals. In addition it examines the differences in homesickness between military and civil employees across the variables of gender, education, age, marital status and family type.…”
mentioning
confidence: 99%
“…On the social front, it facilitates equal and fair opportunities for all and eliminates stereotyping and prejudice against a specific group or category of people. Workforce diversity is also recommended as an indirect persuasion towards an egalitarian society (Garg et al , 2021). From a business perspective, employee diversity promotes diverse ideas, perspectives, ways of working and cognition styles, which breed innovation and creativity.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have concluded that different generations develop distinct differences and characteristics (Rank and Contreras, 2021; Twenge, 2010; Rudolph et al , 2020; Lang, 2020). Previous studies have reported significant generation-based variations in employee’s attitudes (Alferjany and Alias, 2020), homesickness (Garg et al , 2021), motivational drives (Wong et al , 2008), learning orientation (D’Amato and Herzfeldt, 2008), work motivation (Deal Stawiski et al , 2013), career types and success (Dries et al , 2008), etc. Although adequate studies have explored generational differences at the workplace, there is a call to examine significantly internalized, personalized and latent traits and emotions such as spirituality, gratitude, appreciation, compassion and happiness among employees of different generational cohorts.…”
Section: Introductionmentioning
confidence: 99%